Daily Aspirin Use Does Not Impact Clinical Outcomes in Patients With Inflammatory Bowel Disease. Issue 2 (27th March 2020) - Patel, Parita; Gao, Guimin; Gulotta, George; Dalal, Sushila; Cohen, Russell D; Sakuraba, Atsushi; Rubin, David T; Pekow, Joel
Abstract: Background: Although several studies have associated the use of nonsteroidal anti-inflammatory drugs with disease flares in patients with inflammatory bowel disease (IBD), little is known about the impact of daily aspirin use on clinical outcomes in patients with IBD. Methods: We conducted a retrospective analysis of a prospectively collected registry of patients with IBD from May 2008 to June 2015. Patients with any disease activity with daily aspirin use were matched 1:4 to controls by age, sex, disease, disease location, and presence of cardiac comorbidity. Patients with at least 18 months of follow-up were included in the final analysis. The primary outcomes of interest were having an IBD-related hospitalization, IBD-related surgery, and requiring corticosteroids during the follow-up period. Results: A total of 764 patients with IBD were included in the analysis, of which 174 patients were taking aspirin. There was no statistical difference in age, gender, diagnosis (Crohn's disease vs ulcerative colitis), disease duration, Charlson Comorbidity Index, smoking status, medication usage, or baseline C-reactive protein between groups. After controlling for covariables and length of follow-up in the entire population, aspirin use was not associated with a risk of being hospitalized for an IBD-related complication (odds ratio [OR], 1.46; P = 0.10), corticosteroid use (OR, 0.99; P = 0.70), or having an IBD-related surgery (OR, 0.99; P = 0.96). Conclusion: In this single-center analysis, aspirin use did not impact major clinical outcomes in patients with IBD. Although the effect of aspirin use on mucosal inflammation was not directly assessed in this study, these findings support the safety of daily aspirin use in this population.